Corporate Governance Development with E-voting Services - B. S. Bataeva (Управленческие науки)
The paper discribes the method of remote voting at shareholders meetings via the Internet. The methodology of the study is based on the theory of agent costs. It means that costs associated with the exercise of control are important to investors within making investment decisions. The author considers conditions to the digitalization of voting processes: the Russian legislative framework; Internet access in the country; development of digital voting services; the provision of remote voting services by registrars and the Information Disclosure Center of JSC National Settlement Depository. The paper presents results of the analysis of the practice of using electronic voting services in Russian public companies. It has been proved that the creation of the Internet voting infrastructure has contributed to the activity growth of shareholders’ participation in Annual General Meetings. This, in turn, has a positive effect on the quality of corporate governance in these companies. The theoretical and practical significance of the study is to generalize the practice of using electronic voting technology in Russian corporations.